1984
DOI: 10.3168/jds.s0022-0302(84)81501-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactation on Diurnal Temperature Patterns of Dairy Cattle in Hot Environments

Abstract: Vaginal temperature patterns were obtained from 15 Holstein cows through radiotelemetry. Animals were divided into three groups with five animals per group: 1) cows in early lactation, less than 100 days postpartum, 2) cows in late lactation, greater than 240 days postpartum, and 3) dry cows. Animal temperatures, dry bulb, wet bulb, and black globe temperatures were monitored every 15 min for 17 days. Analysis of variance showed no significant difference for daily mean vaginal temperature between lactation gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
4
26
1
1
Order By: Relevance
“…This is caused by higher heat production of high-yield cow's intensive metabolism (Purwanto et al, 1990). Also work of Araki et al (1984) suggest that the body temperature of cattle is very sensitive to changes of surrounding temperature which also supports results of this work.…”
Section: Results and Disscusionsupporting
confidence: 83%
“…This is caused by higher heat production of high-yield cow's intensive metabolism (Purwanto et al, 1990). Also work of Araki et al (1984) suggest that the body temperature of cattle is very sensitive to changes of surrounding temperature which also supports results of this work.…”
Section: Results and Disscusionsupporting
confidence: 83%
“…Such rhythms have been identified in a number of studies on core, vaginal and rectal temperatures (Wrenn et al 1961;Araki et al 1984Araki et al , 1987Lefcourt et al 1999). The resolution of the 2-h measurements does not enable a more detailed analysis of udder temperature fluctuations to determine if any ultradian rhythms existed.…”
Section: Studymentioning
confidence: 99%
“…These results are in accordance with our previous observations on lactating camels (Ayadi et al, 2012), where teat Ts decreased (-1.1 o C) immediately after milking. Nevertheless, the discrepancy between our studies and those carried out on other dairy animals can partially be explained by the differences in the environmental thermal conditions, the age, the physiological status and the teat vasculatisation of the animals, the characteristics of the machine milking system, as well as the milking management (Araki et al, 1984;Eichel, 1992;Kunc et al, 2000Kunc et al, , 2002 et al, 2008;Mala et al, 2009). Therefore, further studies are required to evaluate udder responses using different machine milking systems under different environmental conditions in dairy camels.…”
Section: Machine Milking In Lactating Camelsmentioning
confidence: 54%
“…However, the obtained results indicated that introducing the machine milking had no effect on the thermophysiological parameters of dairy camels maintained under an intensive system. This conclusion was demonstrated by the absence of any dis- Araki et al (1984) reported a decrease in body (vaginal) temperature of dairy cattle immediately after milking and for several hours after animals were sent back to their pens. However, the authors attributed this decrease to the premilking udder wash or to the shade offered by the milking parlour.…”
Section: Biothermal Measurementsmentioning
confidence: 96%